The Crisis of Consciousness and the Specifics of Dramatic Disastrophy in Monodra - Togjan, Nurjanova (Indonesian Journal of Social Development, 2024)
The proposed article is devoted to the theoretical understanding of the concept of monodrama. The main attention is paid to clarifying the features of the development of the action in the monodrama, as well as the specific features of its plot and chronotope. Based on this, the question of the organic presence of monodrama within drama as a kind of literature is solved. In the article, we come to the conclusion that the concept of catastrophe as an important structural element of a dramatic action can also be applied to monodrama. However, this catastrophe occurs not in the external world, but within the consciousness of the central character, and becomes not an object of joint observation (from the point of view of "witness and judge") from the audience (as in a non-monodramatic play). It is directly constructed "here and now" (in "true sympathy") and in the recipient's own mind, inevitably leading to provocative, simultaneous with the hero, "reforming" his system of life values.